Implementation of active and passive control systems in laboratorial and real structures - Carlos Moutinho (2010)
This paper describes the research work on the topic of Structural Control developed in the lastyears at the Civil Engineering Department of the Faculty of Engineering of University of Porto(FEUP), in the context of the research and consultancy activities performed at the Laboratoryof Vibrations and Structural Monitoring (VIBEST). It is described the conception and theimplementation of several control devices in structures, as well as some experimental tests inorder to verify the real efficiency of the proposed control systems. It is covered a significantnumber of control techniques, including passive and active systems and it is emphasized theadvantages and drawbacks found in its application. The numerical and experimental studiesinvolve not only laboratorial physical models with several degrees of complexity, but alsosome real structures using real control systems, with particular interest to the case of thecontrol of vertical and lateral vibrations in footbridges.